Reconstructing the Face of War. Issue 7 (5th July 2019) - Farber, Scott J; Latham, Kerry P; Kantar, Rami S; Perkins, Jonathan N; Rodriguez, Eduardo D
Abstract: Introduction: Ongoing combat operations in Iraq, Afghanistan, and other theaters have led to an increase in high energy craniomaxillofacial (CMF) wounds. These challenging injuries are typically associated with complex tissue deficiencies, evolving areas of necrosis, and bony comminution with bone and ballistic fragment sequestrum. Restoring form and function in these combat-sustained CMF injuries is challenging, and frequently requires local and distant tissue transfers. War injuries are different than the isolated trauma seen in the civilian sector. Donor sites are limited on patients with blast injuries and they may have preferences or functional reasons for the decisions to choose flaps from the available donor sites. Methods: A case series of patients who sustained severe combat-related CMF injury and were treated at Walter Reed National Military Medical Center (WRNMMC) is presented. Our study was exempt from Institutional Review Board review, and appropriate written consent was obtained from all patients included in the study for the use of representative clinical images. Results: Four patients treated by the CMF team at Walter Reed National Military Medical Center are presented. In this study, we highlight their surgical management by the CMF team at WRNMMC, detail their postoperative course, and illustrate the outcomes achieved using representative patient clinical images. We also supplement this case series demonstrating military approaches to complex CMF injuries with CMF reconstructive algorithms utilized by the senior author (EDR) in the management of civilian complex avulsive injuries of the upper, mid, and lower face are thoroughly reviewed. Conclusion: While the epidemiology and characteristics of military CMF injuries have been well described, their management remains poorly defined and creates an opportunity for reconstructive principles proven in the civilian sector to be applied in the care of severely wounded service members. The War on Terror marks the first time that microsurgery has been used extensively to reconstruct combat sustained wounds of the CMF region. Our manuscript reviews various options to reconstruct these devastating CMF injuries and emphasizes the need for steady communication between the civilian and military surgical communities to establish the best care for these complex patients.